2012
DOI: 10.1182/blood-2012-04-424226
|View full text |Cite
|
Sign up to set email alerts
|

Human basophils interact with memory T cells to augment Th17 responses

Abstract: Basophils are a rare population of granulocytes that have long been associated with IgE-mediated and Th2-associated allergic diseases. However, the role of basophils in Th17 and/or Th1 diseases has not been reported. In the present study, we report that basophils can be detected in the mucosa of Th17-associated lung and inflammatory bowel disease and accumulate in inflamed colons containing large quantities of IL-33. We also demonstrate that circulating basophils increased memory Th17 responses. Accordingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 53 publications
2
52
0
1
Order By: Relevance
“…In addition to allergic diseases, basophils have been shown to contribute to several disease states, such as autoimmunity and inflammatory disorders (Rodriguez Gomez et al 2014). For instance, Wakahara et al recently detected basophils in the mucosa of human Th17-associated lung and inflammatory bowel disease (Wakahara et al 2012). This study thus highlighted that basophils were not restricted to the well-known Th2 immune response involved in allergic disease or against helminths.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to allergic diseases, basophils have been shown to contribute to several disease states, such as autoimmunity and inflammatory disorders (Rodriguez Gomez et al 2014). For instance, Wakahara et al recently detected basophils in the mucosa of human Th17-associated lung and inflammatory bowel disease (Wakahara et al 2012). This study thus highlighted that basophils were not restricted to the well-known Th2 immune response involved in allergic disease or against helminths.…”
Section: Discussionmentioning
confidence: 97%
“…Huber et al recently showed that IL-3-activated basophils could enhance monocyte derived DCs survival (Huber et al 2014) however whether this effect was statistically significant and was RANKL-dependent was not assessed. As basophils were recently shown to enhance IL-17 and IFN-␥ production in memory CD4+ T cells (Wakahara et al 2012), it would be also interesting to assess the potential role of RANKL during basophil-T cell interaction. However, as activated T cells also express RANKL, this will be difficult to demonstrate especially in human.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells have been shown to be important mediators in some animal models of arthritis and have been found to be increased in the synovium of patients with rheumatoid arthritis; however, it is still not clear whether they are key players in the disease 27 28. Basophils may also play a role, and it was recently shown that histamine release from basophils amplifies IL-17 release from T cells 29. It is important to note that the H 4 R has a very high affinity for histamine, especially compared with the histamine H 1 and H 2 receptors, and therefore it may be activated by cells that release even low levels of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a reduction in IL-17 levels via H 4 receptor blockade has been noted in mouse models of asthma, dermatitis, and arthritis (Dunford et al, 2006;Cowden et al, 2010bCowden et al, , 2014. Basophils have been implicated in enhancing Th17 responses in humans, and this effect appears to be mediated by H 2 receptor and H 4 receptor (Wakahara et al, 2012). In human neutrophils, engagement of the H 4 receptor blocked the adhesion-dependent degranulation, indicating a possible anti-inflammatory effect of the H 4 receptor on these cells (Dib et al, 2014).…”
Section: Functionmentioning
confidence: 99%